2020
DOI: 10.1002/smll.202000733
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive Single Crystal Perovskite–Graphene Hybrid Vertical Photodetector

Abstract: Organolead trihalide perovskites have attracted significant attention for optoelectronic applications due to their excellent physical properties in the past decade. Generally, both grain boundaries in perovskite films and the device structure play key roles in determining the device performance, especially for horizontal‐structured device. Here, the first optimized vertical‐structured photodetector with the perovskite single crystal MAPbBr3 as the light absorber and graphene as the transport layer is shown. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 59 publications
2
55
0
Order By: Relevance
“…Direct-bandgap perovskites have a long carrier lifetime by tens to hundreds of nanoseconds [108] and even up to >1 μs [5,119]. Zou et al [174] reported a vertical structure with a short electrode distance of ~2.3 μm, which enables effective charge extraction and high photoresponsivity of >1000 A W −1 at a low incident intensity of 0.66 mW cm −2 and a bias voltage of 3 V. Its photoconductive gain is approximately 2.37 × 10 3 , which is attributed to the fast charge transfer and long carrier recombination lifetime.…”
Section: Reviewsmentioning
confidence: 99%
“…Direct-bandgap perovskites have a long carrier lifetime by tens to hundreds of nanoseconds [108] and even up to >1 μs [5,119]. Zou et al [174] reported a vertical structure with a short electrode distance of ~2.3 μm, which enables effective charge extraction and high photoresponsivity of >1000 A W −1 at a low incident intensity of 0.66 mW cm −2 and a bias voltage of 3 V. Its photoconductive gain is approximately 2.37 × 10 3 , which is attributed to the fast charge transfer and long carrier recombination lifetime.…”
Section: Reviewsmentioning
confidence: 99%
“…Graphene was used as the transport layer to enhance the carrier mobility of the photodetector, thus improving the photoelectric performance of the whole device, which the structure is illustrated (Figure 7c,d). [55] The study on the influence of halide element doping has also become a hot topic. Venkata et al have prepared MAPbI 3Àx Br x thin film by chemical vapor deposition method and comparing that with parent MAPbI 3 thin film, they have concluded that MAPbI 3Àx Br x samples possess better crystalline quality and photoelectric performance under the incident light of 632 nm.…”
Section: Apbx 3 (A ¼ Ma; X ¼ Br I Mixed Halides)mentioning
confidence: 99%
“…Photoresponse speed is another key parameter of the photodetector, which is extremely important in photoresponse communication systems. [63,64] The response speeds of the Ag 2 S-QDiP (1280)-based photodetector under both visible (532 nm) and NIR (1064 nm) band are evaluated via the time-dependent photoresponse curves. As shown in Figure S14a,c (Supporting Information), the time-dependent photoresponse curves demonstrate that the sensitivity to the incident light of both visible and NIR bands is repeatable and stable.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%